2016
DOI: 10.3847/0004-637x/823/1/32
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry Between Galaxies With Clockwise Handedness and Counterclockwise Handedness

Abstract: While it is clear that spiral galaxies can have different handedness, galaxies with clockwise patterns are assumed to be symmetric in all of their other characteristics to galaxies with counterclockwise patterns. Here we use data from SDSS DR7 to show that photometric data can distinguish between clockwise and counterclockwise galaxies. Pattern recognition algorithms trained and tested using the photometric data of a clean manually crafted dataset of 13,440 spiral galaxies with z < 0.25 can predict the handedn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
142
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(163 citation statements)
references
References 28 publications
21
142
0
Order By: Relevance
“…The experiment using the dataset of galaxies that were annotated in a fully automatic process provided a comparable handedness prediction accuracy of ∼65%. The analysis also revealed that several different photometric measurements such as the SDSS 'Stokes U' parameter exhibit a statistically significant difference between clockwise and counterclockwise galaxies (Shamir 2016).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…The experiment using the dataset of galaxies that were annotated in a fully automatic process provided a comparable handedness prediction accuracy of ∼65%. The analysis also revealed that several different photometric measurements such as the SDSS 'Stokes U' parameter exhibit a statistically significant difference between clockwise and counterclockwise galaxies (Shamir 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Linear regression is applied across the vertical lines of the radial intensity plot for each group of peaks, and the sign of the slopes reflect the direction of the arm, therefore determining the handedness of the galaxy. The algorithm is described in details and numerous examples in (Shamir 2011b;Hoehn & Shamir 2014;Shamir 2012), and the process of galaxy classification is described in (Shamir 2016).…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations